Antiviral Effects and Underlying Mechanisms of Probiotics as Promising Antivirals - Wang, Yanjin; Moon, Assad; Huang, Jingshan; Sun, Yuan; Qiu, Hua-Ji (Frontiers in Cellular and Infection Microbiology, 2022)
Probiotics exert a variety of beneficial effects, including maintaining homeostasis and the balance of intestinal microorganisms, activating the immune system, and regulating immune responses. Due to the beneficial effects of probiotics, a wide range of probiotics have been developed as probiotic agents for animal and human health. Viral diseases cause serious economic losses to the livestock every year and remain a great challenge for animals. Moreover, strategies for the prevention and control of viral diseases are limited. Viruses enter the host through the skin and mucosal surface, in which are colonized by hundreds of millions of microorganisms. The antiviral effects of probiotics have been proved, including modulation of chemical, microbial, physical, and immune barriers through various probiotics, probiotic metabolites, and host signaling pathways. It is of great significance yet far from enough to elucidate the antiviral mechanisms of probiotics. The major interest of this review is to discuss the antiviral effects and underlying mechanisms of probiotics. More underlying mechanisms of probiotics need to be dissected to provide targets for the development of novel antivirals.